2012
DOI: 10.1371/journal.pone.0032818
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Hydroxyapatite with Proteins and Its Toxicological Effect to Zebrafish Embryos Development

Abstract: The increased application of nanomaterials has raised the level of public concern regarding possible toxicities caused by exposure to nanostructures. The interactions of nanosized hydroxyapatite (HA) with cytochrome c and hemoglobin were investigated by zeta-potential, UV-vis, fluorescence and circular dichroism. The experimental results indicated that the interactions were formed via charge attraction and hydrogen bond and obeyed Langmuir adsorption isotherm. The two functional proteins bridged between HA par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 40 publications
3
32
2
Order By: Relevance
“…The results in Figure 4B showed that the pericardial edema and tail malformation occurred as common malformations observed in embryos exposed to SiNPs. Similar with our results, Xu and coworkers reported that serious malformations of pericardial edema and yolk sac edema were found in embryos treated with titanium dioxide nanoparticles [33]. While fin fold and tail abnormalities were observed as the most common ones when embryos incubating with sliver nanoparticles [34].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results in Figure 4B showed that the pericardial edema and tail malformation occurred as common malformations observed in embryos exposed to SiNPs. Similar with our results, Xu and coworkers reported that serious malformations of pericardial edema and yolk sac edema were found in embryos treated with titanium dioxide nanoparticles [33]. While fin fold and tail abnormalities were observed as the most common ones when embryos incubating with sliver nanoparticles [34].…”
Section: Discussionsupporting
confidence: 91%
“…The chorion possess pore canals is to be approximately 0.5–0.7 µm in diameter, meaning that the size of chorion pore canals are larger than the common size of nanoparticles [46]. However, some studies have reported that the nano-SiO 2 is mainly adsorbed on the out surface of chorion, which might affect the nutrient absorption and vitamin synthesis [16], [17]. In the present study, our data showed that exposure to silica nanoparticles caused the inhibition of hatching rate, which led to a direct delay of embryos development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxicity, inflammation and increased oxidative stress through reactive oxygen species (ROS) formation are prominently discussed to be relevant factors regarding the safety of small particles down to the nano-range (Knaapen et al 2004;Unfried et al 2007;Lewinski et al 2008;Turkez 2008 and2011). It has been reported that different sizes and morphologies of NPs have the potential to influence the interaction with many kind of biomolecules, including proteins, enzymes and DNA (Grandjean-Laquerriere et al 2005;Ramesh et al 2007;Xu et al 2012). The liver was considered as a target site for nanotoxicity due to its accumulative properties after ingestion, inhalation or absorption (Wang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxicity, inflammation and increased oxidative stress through reactive oxygen species (ROS) formation are prominently discussed to be relevant factors regarding the safety of small particles down to the nano-range (Knaapen et al 2004;Unfried et al 2007;Lewinski et al 2008;Turkez 2008Turkez , 2011. It has been reported that different sizes and morphologies of nanoparticles have the potential to influence the interaction with many kinds of biomolecules including proteins, enzymes and DNA (GrandjeanLaquerriere et al 2005;Ramesh et al 2007;Xu et al 2012). Moreover, the liver was considered a target site for NP toxicity, due to NP accumulation within it after ingestion, inhalation or absorption .…”
Section: Introductionmentioning
confidence: 99%